2022
DOI: 10.1016/j.dadr.2022.100027
|View full text |Cite
|
Sign up to set email alerts
|

Similar COVID-19 incidence to the general population in people with opioid use disorder receiving integrated outpatient clinical care

Abstract: Introduction : During the COVID-19 pandemic, limited access to health care augmented COVID-19 risk in subjects with opioid use disorder (OUD). The aim of the study was to compare COVID-19 incidence in individuals with OUD receiving continuous clinical care with that of the general population. Methods : A prospective cohort study was carried out from March 2020 to March 2021 comparing COVID-19 cumulative incidence of individuals presenting an OUD receiving integrated cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Similarly, a study by Lindquist and colleagues found a lower prevalence of SARS-CoV-2 among people with SUD attending a needle exchange program in Stockholm (28) when comparing to the prevalence of SARS-CoV-2 found in a study on healthy blood donors from the same region and period (29). A study by Vallecillo and colleagues, found a similar incidence of COVID-19 among patients on OAT (30) compared to an age-reference general population (31).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, a study by Lindquist and colleagues found a lower prevalence of SARS-CoV-2 among people with SUD attending a needle exchange program in Stockholm (28) when comparing to the prevalence of SARS-CoV-2 found in a study on healthy blood donors from the same region and period (29). A study by Vallecillo and colleagues, found a similar incidence of COVID-19 among patients on OAT (30) compared to an age-reference general population (31).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, a study by Lindquist and colleagues found a lower prevalence of SARS-CoV-2 among people with SUD attending a needle exchange program in Stockholm [ 41 ] when comparing to the prevalence of SARS-CoV-2 found in a study on healthy blood donors from the same region and period [ 42 ]. A study by Vallecillo and colleagues, found a similar incidence of COVID-19 among patients on OAT [ 43 ] compared to an age-reference general population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The centers belonged to the public health system and received individuals from two different districts of Barcelona and from the metropolitan area, respectively. Functioning of the centers has been published elsewhere [35].…”
Section: Methodsmentioning
confidence: 99%